Productivity, Capital-Intensity and Labour Quality at Sector Level in New Zealand and the UK - Geoff Mason; Matthew Osborne (New Zealand Government, The Treasury, 2007)
Understanding productivity performance is important to informing policy advice on how to improve productivity and therefore New Zealand's overall economic performance. Given data limitations inherent in international productivity comparisons, this paper is not intended to inform policy in isolation but forms an important element of a wide and expanding body of evidence on the performance of the New Zealand economy. Previous international productivity comparisons involving New Zealand have been confined to the aggregate economy or to broadly-defined sectors such as manufacturing. This paper reports on a New Zealand-UK comparison which distinguishes 21 different `market sectors' (ie, excluding public administration, education, health, property services and some personal, social and community services). It confirms the prevailing consensus that, in aggregate, New Zealand market sectors compare unfavourably with the UK on average labour productivity (ALP) - and by implication compare even more unfavourably with other countries such as the US. However, beneath this overall story there is considerable sectoral variation. While some NZ sectors out-perform the UK on ALP and/or multi-factor productivity (MFP), there is a large group of sectors which fall short of the UK on both productivity measures. Most of these low-productivity sectors are relatively low in physical capital-intensity compared to the UK. Overall, roughly a quarter of the New Zealand-UK gap in ALP for aggregate market sectors in 2002 was attributable to differences in employment structure such as the relatively high shares of New Zealand employment in comparatively low value added sectors such as agriculture. The remaining three quarters of the ALP gap were accounted for by within-sector productivity differences.
Keywords: J24; O47; P52; 330; productivity; capital-deepening; human capital; Arbeitsproduktivität; Humankapital; Wirtschaftsstruktur; Vergleich; Neuseeland; Großbritannien